Improvement On Transient Response Of Pneumatic Grasper Robot Positioning Using Deadzone Compensator - Muhamad Saiful Azrin, Abdul Ghani (2022)
This project presents the design and modeling dead zone compensator with the close-loop control of pneumatic robot grasper unit. Pneumatic system is a very common devices in industrial automation application due to the advantage such as easy and simple maintenance. However, there are some challenges and limitation in application due to its non-linearities with uncertain behavior including dead zone influences. Dead zone is referring certain input control valve values give no response to the valve operations as the pressure flow is blocked. Therefore, this study has taken initiative to propose the method to compensate with the dead zone effect such by using inverse dead zone function approaches. The identification works are done to identifying the characteristic of the pneumatic system used on the targeted platform; tri-finger pneumatic grippers (TPG). Moreover, the data from dead zone analysis was used to design the compensator equation and apply to the PID controller as selected controller. The result shows that the offset value is close to the center, and the dead zone values on both sides are balanced. The proposed compensator. The experiment carried on targeted platform to validate the proposed compensator with the controller without the compensator. The result shows that the PID control system with compensator have improved the transient response of a fingertip positioning for the TPG system.